Complications after a Bidirectional Cavopulmonary Anastomosis with Accessory Sources of Pulmonary Blood Flow - Martínez-Quintana, Efrén; Rodríguez-González, Fayna (International Journal of Angiology, 2016)
Creating an accessory source of pulsatile pulmonary blood flow in a patient with a bidirectional cavopulmonary anastomosis may have advantages and disadvantages. In relation to the latter, we report the complications seen in a cyanotic congenital heart disease patient who developed a superior vena cava syndrome plus severe swelling of his right hand that evolved satisfactorily after percutaneous and medical treatment.
Keywords: fistula; superior vena cava syndrome; ulceration